2019
DOI: 10.1016/j.gpb.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Inulin Can Alleviate Metabolism Disorders in ob/ob Mice by Partially Restoring Leptin-Related Pathways Mediated by Gut Microbiota

Abstract: Inulin has been used as a prebiotic to alleviate glucose and lipid metabolism disorders in mice and humans by modulating the gut microbiota . However, the mechanism underlying the alleviation of metabolic disorders by inulin through interactions between the gut microbiota and host cells is unclear. We use ob/ob mice as a model to study the effect of inulin on the cecal microbiota by 16S rRNA gene amplicon sequencing and its interaction with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 61 publications
(72 reference statements)
13
90
0
Order By: Relevance
“…Prevotella possesses enzymes that can degrade cellulose and xylan to produce propionate used for host [48]. What's more, the previous study reported that the abundance of Prevotellaceae_ UCG_001 was negatively correlated with the blood parameters about glucose and lipid [49]. It was thus speculated that Prevotellaceae_UCG_001 might contribute to the host glucose and lipid metabolism through the production of propionate.…”
Section: Discussionmentioning
confidence: 98%
“…Prevotella possesses enzymes that can degrade cellulose and xylan to produce propionate used for host [48]. What's more, the previous study reported that the abundance of Prevotellaceae_ UCG_001 was negatively correlated with the blood parameters about glucose and lipid [49]. It was thus speculated that Prevotellaceae_UCG_001 might contribute to the host glucose and lipid metabolism through the production of propionate.…”
Section: Discussionmentioning
confidence: 98%
“…Inulin has been used as a prebiotic to alleviate metabolic disorders, such as obesity and diabetes by modulating the gut microbiota [28][29][30]. The present study was performed to assess the long-term influences of inulin on experimental hyperuricemic mice and its possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may explain the changes in hepatic lipid content. The butyrate produced in intestinal lumen, which is an energy source for colonocytes, can activate the AMPK signalling pathway in intestinal epithelium, inhibiting hepatic cholesterol and fatty acids synthesis (Gao et al., 2019; Rumberger, Arch, & Green, 2014; Song et al., 2019). In our study, a combined wheat bran fibre and inulin diet feeding tended to reduce the butyrate concentrations in colon, which may lead to a reduced inhibition of hepatic lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that fibre‐enriched diets may positively influence host lipid metabolism and improve metabolic syndrome via increasing the short‐chain fatty acids (SCFAs) concentrations in the gut (Anderson et al., 2009; Ruderman, Carling, Prentki, & Cacicedo, 2013; Song et al., 2019). However, several studies showed that the addition of dietary fibres, especially fermentable fibres, will lead to hepatic dysfunction and liver inflammation (Singh et al., 2018; Zhu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%